Effects of a wide range of dietary nicotinamide riboside (NR) concentrations on metabolic flexibility and white adipose tissue (WAT) of mice fed a mildly obesogenic diet. Issue 8 (13th April 2017) - Shi, Wenbiao; Hegeman, Maria A.; van Dartel, Dorien A.M.; Tang, Jing; Suarez, Manuel; Swarts, Hans; van der Hee, Bart; Arola, Lluis; Keijer, Jaap
Abstract : To determine the optimal concentration of vitamin B3 in the diet, a wide range of nicotinamide riboside (NR) was given to C57Bl/6JRcc mice. A defined human relevant diet with low tryptophan levels was used. Metabolic flexibility, serum parameters and white adipose tissue were examined. Surprisingly the effects were small. 30 mg NR/kg diet was most beneficial for metabolic health. Abstract : Scope: Metabolic flexibility is the ability to switch metabolism between carbohydrate oxidation (CHO) and fatty acid oxidation (FAO) and is a biomarker for metabolic health. The effect on metabolic health of nicotinamide riboside (NR) as an exclusive source of vitamin B3 is unknown and is examined here for a wide range of NR. Design and methods: Nine‐week‐old male C57BL/6JRcc mice received a semi‐purified mildly obesogenic (40 en% fat) diet containing 0.14% L‐tryptophan and either 5, 15, 30, 180, or 900 mg NR per kg diet for 15 weeks. Body composition and metabolic parameters were analyzed. Metabolic flexibility was measured using indirect calorimetry. Gene expression in epididymal white adipose tissue (eWAT) was measured using qRT‐PCR . Results: The maximum delta respiratory exchange ratio when switching from CHO to FAO (maxΔRERCHO1→FAO ) and when switching from FAO to CHO (maxΔRERFAO→CHO2 ) were largest in 30 mg NR per kg diet (30NR). In eWAT, the gene expression of Pparγ, a master regulator of adipogenesis, and of Sod2 and Prdx3, two antioxidant genes, were significantly upregulated in 30NR compared to 5NR. Conclusion: 30NR is most beneficial for metabolic health, in terms of metabolic flexibility and eWAT gene expression, of mice on an obesogenic diet.